PROTEOMIC ANALYSIS OF DIFFERENT EXTRACTS FROM AMARANTH (AMARANTHUS TRICOLOR) GRAINS. - SRIVASTAVA, REEMA; ROY, BIJOY K. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Amaranth seed has a high nutritional value due to the balanced composition of its protein fractions (i.e albumins, globulins, prolamins and glutelins). These were isolated by sequential extractions. The amount of albumins, globulins, prolamins and glutelins were 2.90, 2.20, 0.47 and 5.73 g/100g of seed flour. Upon electrophoresis, albumins were found to be most polymorphic, while prolamins were made up of fewer and less abundant components. Gel electrophoresis analysis revealed the occurrence of glutelins as the major proteins in the seed. Amaranth protein isolates were prepared by (a) extraction at different alkaline pHs and precipitation at pH 5 and (b) extraction at pH 9 and precipitation at different pHs. The isolates were compared with protein fractions. Acidification at pH 5 and precipitation at lower pHs lead to denaturation of the proteins which was partially reversed by returning to pH 7.